Intracellular nanoscale architecture as a master regulator of calcium carbonate crystallization in marine microalgae - Kadan, Yuval; Tollervey, Fergus; Varsano, Neta; Mahamid, Julia; Gal, Assaf (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Unicellular marine microalgae are responsible for one of the largest carbon sinks on Earth. This is in part due to intracellular formation of calcium carbonate scales termed coccoliths. Traditionally, the influence of changing environmental conditions on this process has been estimated using poorly constrained analogies to crystallization mechanisms in bulk solution, yielding ambiguous predictions. Here, we elucidated the intracellular nanoscale environment of coccolith formation in the model species Pleurochrysis carterae using cryoelectron tomography. By visualizing cells at various stages of the crystallization process, we reconstructed a timeline of coccolith development. The three-dimensional data portray the native-state structural details of coccolith formation, uncovering the crystallization mechanism, and how it is spatially and temporally controlled. Most strikingly, the developing crystals are only tens of nanometers away from delimiting membranes, resulting in a highly confined volume for crystal growth. We calculate that the number of soluble ions that can be found in such a minute volume at any given time point is less than the number needed to allow the growth of a single atomic layer of the crystal and that the uptake of single protons can markedly affect nominal pH values. In such extreme confinement, the crystallization process is expected to depend primarily on the regulation of ion fluxes by the living cell, and nominal ion concentrations, such as pH, become the result, rather than a driver, of the crystallization process. These findings call for a new perspective on coccolith formation that does not rely exclusively on solution chemistry.